2011
DOI: 10.3354/ame01518
|View full text |Cite
|
Sign up to set email alerts
|

Species-specific patterns in the vulnerability of ­carbon-starved bacteria to protist grazing

Abstract: Many heterotrophic bacteria possess adaptations for prolonged survival under carbon and energy limitation, generally involving a reduction in cell size and an increased resistance to environmental stress factors. In order to reveal whether carbonstarved bacteria also become less vulnerable to protist grazing, we compared the growth of a bacterivorous nanoflagellate, Cafeteria roenbergensis, on different physiological states of 3 bacterial strains with well-studied starvation responses (Vibrio vulnificus, Photo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 60 publications
(43 reference statements)
1
8
0
Order By: Relevance
“…Note, our errors here and throughout the rest of the paper refer to standard deviations after accounting for propagation of uncertainty [ 23 ]. The estimated host doubling time is h, which is consistent with the previous reported range of 3.3–8.3 h [ 24 ].…”
Section: Resultssupporting
confidence: 90%
“…Note, our errors here and throughout the rest of the paper refer to standard deviations after accounting for propagation of uncertainty [ 23 ]. The estimated host doubling time is h, which is consistent with the previous reported range of 3.3–8.3 h [ 24 ].…”
Section: Resultssupporting
confidence: 90%
“…The major predators of bacteria in aquatic systems are heterotrophic and mixotrophic nanoflagellates. Since the recognition of this important predator-prey interaction, many aquatic nutrient dynamics studies have focused on understanding factors that affect predation on bacteria, with particular attention given to the process of prey identi -fication and selection (Pernthaler 2005, Anderson et al 2011.…”
Section: Introductionmentioning
confidence: 99%
“…However, contrary to expectations, the non-growing bacteria were selectively cropped, while the rapidly growing bacteria were not significantly diminished. Anderson et al (2011) recently suggested that protists may have different responses to growth state of their prey and that these responses may depend on prey species.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, if small size (i.e., Ͻ0.5 m) constitutes a refuge against grazing, Actinobacteria may be negatively selected only in appearance, either because the limiting size might be an evolved defense mechanism (and thus cells tend to be smaller than those in other groups) or, on the contrary, because preference by grazers is so high that the group is permanently confined to the small-size refuge. It has been suggested that cell miniaturization alone is not sufficient to explain grazing avoidance (48) and that other resistance mechanisms, such as wall structures present in Gram-positive Actinobacteria, are involved in determining a limited edibility (49). Research on prokaryotic grazing is still in its infancy, but our results indicate that random grazing cannot be the paradigm.…”
Section: Discussionmentioning
confidence: 45%